2011
DOI: 10.1007/s11302-011-9267-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical phenotypes of P2X2 purinoreceptor immunoreactive cell bodies in the area postrema

Abstract: Purines such as adenosine 5′-triphosphate (ATP) act as extracellular messengers through specific purinergic receptors. Three different classes of purinergic receptors have been identified and termed P1, P2X, and P2Y. The purinergic receptor subunit P2X2 is a ligand-gated ion channel that is widely expressed by neurons in the CNS. In the brainstem medulla oblongata, the ionotropic P2X2 receptor (P2X2R) is enriched in the area postrema (AP). Two different antisera to P2X2R were used to determine the chemical nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Neurons containing GABA, substance P, enkephalin, neurotensin, cholecystokinin, orexin, dynorphin, as well as serotonincontaining neurons, have also been identified by immunohistochemistry (Armstrong et al, 1981;Newton and Maley, 1984;Maley, 1985a, 1985b;Newton et al, 1985;Guan et al, 2005;Mangano et al, 2012). Some of the serotonin-containing neurons have been shown to connect to the lateral parabrachial nucleus (Lanca and van der Kooy, 1985).…”
Section: Neuroendocrine Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons containing GABA, substance P, enkephalin, neurotensin, cholecystokinin, orexin, dynorphin, as well as serotonincontaining neurons, have also been identified by immunohistochemistry (Armstrong et al, 1981;Newton and Maley, 1984;Maley, 1985a, 1985b;Newton et al, 1985;Guan et al, 2005;Mangano et al, 2012). Some of the serotonin-containing neurons have been shown to connect to the lateral parabrachial nucleus (Lanca and van der Kooy, 1985).…”
Section: Neuroendocrine Aspectsmentioning
confidence: 99%
“…Binding sites/receptors for amylin (Sexton et al, 1994), canabinoid CB1 receptor, cholecystokinin CCK-1 receptor (Moran et al, 1986), angiotensin II AT 1 (Lenkei et al, 1997;Allen et al, 2000), atrial natriuretic peptide Saavedra et al, 1992), GLP-1 (Göke et al,1995), Ghrelin-GHRS receptor (Zigman et al, 2006); neuropeptide Y, Peptide YY and pancreatic polypeptide-Y1, Y2, Y4 and Y5 receptors (Martel et al, 1986;Kishi et al, 2005); purinergic P2X2 and P2X7 receptors (Kodama et al, 2007;Mangano et al, 2012), somatostatin (Patel et al, 1986), substance P NK-1 receptor (Baude and Shigemoto, 1998), vasoactive intestinal polypeptide (Shaffer and Moody, 1986), vasopressin (Phillips et al, 1988), and insulin (Werther et al, 1987) have been observed in the area postrema. Like the other sensory CVOs, the area postrema exhibits the CD14 lipopolysacharide receptor (Lacroix et al, 1998).…”
Section: Neuroendocrine Aspectsmentioning
confidence: 99%
“…C1 and C2 represent the rostral extent of A1 and A2 nuclei, respectively. In particular, the caudal extent of A2/C2 area is also known as ala cinerea nucleus which continues caudally to form the so-called area postrema (AP) ( Potes et al, 2010 ; Rinaman, 2011 ; Mangano et al, 2012 ). The constellation of catecholamine nuclei depicted above, corresponds to a few nuclei placed within a small brain region but exerting a widespread influence in the CNS both via descending ( Mason and Fibiger, 1979 ; Hammar et al, 2004 ) and ascending ( Everitt et al, 1983 ) fibers.…”
Section: Introductionmentioning
confidence: 99%